Micropropagation of Acacia Auriculiformis A. Cunn Ex Benth from Different Explant Sources - Ismail, Haliza (2000)
Acacia auriculiformis is one of the multipurpose tree species under Leguminoceae family which has the capability to fix nitrogen from soil and rehabilitate the land. The wood properties are widely known to be suitable for pulp and paper making and can contribute as raw materials for pulp and paper industry in Malaysia. The large scale propagation of A. auriculiformis using seeds from open pollination will result in high variation of trees. Therefore, micropropagation can be an alternative method to mass propagate A. auriculiformis from selected materials (genetically improved) which can produce higher yield, uniform and high quality wood. This study sought to develop a protocol for micropropagation of A. auriculiformis utilizing samples from different explant sources. The explant sources were from 2 month-old in vitro seedlings, 5 month- old seedlings, 14 month-old trees, 6 year-old plus trees, marcotts of 6 year-old plus tree, 10 year-old plus trees, forced flushed shoots from branch cuttings of 10 year-old trees and coppice shoots from 10 year-old trees.